Application of burnt oil palm shells as granular media filtration for physical and biological contaminants removal in the water treatment process / Noraini Mat Budari - Mat Budari, Noraini (2013)
This study was conducted to discover a new filtering media, specifically for pathogenic microorganism removal for the water treatment industry to produce safe drinking water. Granular bed filtration was used in this study as a healthy, simple and economical method to prevent the penetration of bacterial contamination. Alternative filter media from local source namely the burnt oil palm shell (BOPS) was also introduced. In order to determine the BOPS performance, the experimental programme and research approach used in this study were the design and construction of filtration unit, preparation of filter media, determination distribution size, morphology, porosity and specific gravity of filter media and also physical and biological analysis of filtrate water. In addition, total coliform and Escherichia coli tests of filtrate water in single-, dual- and tri-media filter were also investigated. Physical properties of BOPS were found to be equivalent or superior to those commercialized available granular filter media with ball-pan hardness of 97.30%. Granular media filter with mix media classes (which is a dual-media filtration) is also found to be a reliable surrogate for physical removal and biological barrier during filtration studies. Dual-media filtration BOPS/sand ES 1.0/0.5 mm is operating optimum condition of removing 80.77% of turbidity, 76.23% of suspended solid, 59.45% of colour and for bacteriological 0.63 log and 0.46 log of removal for total coliform and Escherichia coli. There was statistically significance difference between types of media filter to the removal of physical variable at 0.05 level as determined by one-way anova for the turbidity % removal (p = 0.000), suspended solid % removal (p = 0.000) and colour % removal (p = 0.000). Under one-factor analysis, there was a statistically significant difference for dual-media filtration for Escherichia coli removal (p = 0.001), but not significant for single- and tri-media filter. Both Tukey HSD and Scheffe post hoc analysis revealed that BOPS/Sand: 1.0/0.5mm significantly higher log of removal by compared to commercial filter media anthracite/sand. The study also identified that energy losses were correspondingly to the porosity and shape factor value of media filter. Moreover, lower diameter grain size resulted in higher energy losses. The BOPS was identified as a potential filter media that can help in reducing the cost of water treatment and enhancing environmental sustainability. Thus, the final result of this study has found that BOPS can be used as a new biodegradable medium filter in water treatment process specifically for the removal of pathogenic microorganism.